Market Segmentation and Differential Reactions of Local and Foreign Investors to Analyst Recommendations - Jia, Chunxin; Wang, Yaping; Xiong, Wei (Review of Financial Studies, 2017)
This paper uses segmented dual-class shares of Chinese firms—A shares traded in mainland China by local investors and H shares traded in Hong Kong by foreign investors—to document a rich pattern in the differential reactions of local and foreign investors to analyst recommendations. This pattern reveals that social connections between analysts and investors affect investor reactions to analyst recommendations. Because of the investors’ differential reactions, analyst recommendations may exacerbate, rather than attenuate, the market segmentation between the two share classes. Received January 28, 2016; editorial decision October 23, 2016 by Editor Robin Greenwood.